Otological Findings Ten Years after Myringotomy with Tympanostomy Tube Insertion - Ali Goljanian Tabrizi; Seyed Mostafa Hashemi; Behrouz Barati (Iranian Journal of Otorhinolaryngology, 2011)
Introduction: To study the long-term complications of tympanostomy tube insertion in young children 10 years after surgery.   Materials and Methods: In September 2011, the medical records of all patients who had undergone myringotomy with tympanostomy tube insertion between February 2000 and March 2001 at the two general hospitals of Isfahan University of Medical Sciences were studied. Of the 98 patients who fulfilled the inclusion criteria, 82 patients agreed to participate and were enrolled in the study. The complications of the operation were evaluated in these patients.   Results: Of the 164 ears that were operated on, myringosclerosis was found in 17.1%, atrophy of the tympanic membrane in 1.2%, permanent perforation of the tympanic membrane in 0.6% and tympanic membrane atelectasis in 0.6%. None of the patients developed cholesteatoma as a complication of tympanostomy tube insertion.   Conclusion:  Considering the low risk of serious complications after 10 years, tympanostomy tube insertion is a safe and effective treatment option in the treatment of otitis media with effusion.